THE IMPLEMENTATION OF HUMAN RESOURCES (HR) DEVELOPMENT IN BANANA FARMERS IN BLANGSENONG VILLAGE AIMED AT INCREASING PRODUCTION AND SALES RESULTS - Muhammad Ferdiananda Chadafi; Mai Simahatie; Hilda Pratiwi; Sarah Nadia; Cut Bulan Ananda (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2024)
This community service activity aims to implement human resource (HR) development for banana farmers in Blangsenong Village in order to increase production and sales results. Farmers in this village face various obstacles, both in aspects of cultivation techniques and marketing strategies, which have an impact on low productivity and income. Therefore, this program is designed to provide training to farmers in the field of agricultural management, more efficient cultivation techniques, and more effective product marketing. The methods used include direct training, group discussions, and field assistance. The results of this program are expected to be able to improve farmers' skills, optimize banana production results, and open access to wider markets, thereby having a positive impact on farmers' economic welfare. By improving the quality of human resources, farmers are expected to be more independent and competitive in facing the challenges of modern agriculture.